The influence of work commitment and job satisfaction on employee performance in construction companies at PT 'X' - Damayanti, Eka Ari; Sibarani, Mentiana (International Journal Labs, 2024)
The COVID-19 pandemic has had a significant impact on the construction industry in Indonesia, including the high employee turnover rate which has an impact on project productivity and quality. This study aims to analyze the influence of work commitment and job satisfaction on employee performance at PT